The Analysis of Figurative Language in Two Divergent Movie Genres: Semantic Study - Komalasari, Rani; Marwito Wihadi; Yayan Suryana (English Lecturers and Teachers Association (ELTA), 2025)
The purpose of this study was to identify the types and functions of figurative language in two divergent movie genres. The data is taken from utterances from actors or characters in a movie. The method of this study is qualitative research, and the research design is a case study. Observation and note-taking research are the techniques for collecting data for this research to understand utterances and classify types, meanings, and functions. The results of this study showed that the researcher found a total of 48 utterances in comedy movie genres and 9 (nine) types found in the movies, these types include Allegory (16.67%), metaphor (2.08%), metonymy (14.58%), Paradox (8.33%), personification (6.25%), Simile (16.67%), Symbol (6.25%), Synecdoche (6.25%) Hyperbole (22.92%). This research found a total of 26 utterances in horror movie genres and 8 (eight) types found in the movies, these types include Allegory (11.53%), metaphor (3.84), metonymy (19.23%), Simile (23.08%), Symbol (19.23%), Synecdoche (7.72%) Hyperbole (11.53%), Irony (3.84%). The second result identifies the function. The most dominant function found in comedy and horror movies is imaginative pleasure. Keywords : Figurative language, semantic, movie